Granuloma Annulare Mimicking Alopecia Mucinosa in a Child: An Atypical Presentation - Kallolinee Samal; Bhabani S. T. P. Singh; Surabhi Singh; Liza Mohapatra (Indian Journal of Paediatric Dermatology)
Granuloma annulare (GA) is a common, benign, self-limited granulomatous inflammatory dermatosis of undetermined etiology. Subcutaneous GA is typically seen in the pediatric population. It has been described in some atypical presentations resembling dermatofibroma, dermatomyositis, papulonecrotic tuberculid, psoriasis, and tinea cruris, and also a report of GA appearing on a scar and mimicking sarcoidosis present in literature. However, no case has been reported as GA mimicking alopecia mucinosa. We describe a case of a six-year-old child presenting with GA mimicking alopecia mucinosa. The alopecia mucinosa manifests as well-defined erythematous to skin-colored single or multiple plaques or patches of hair loss in head and face regions with histopathological findings of follicular mucinosis affecting most of the follicles. Such case reports remind us to establish a clinicopathologic correlation before diagnosing. Our patient was prescribed topical mometasone furoate 0.1% ointment under occlusion once daily for 30 consecutive days, with a satisfactory decrease in induration and erythema. At seven months, the lesion completely disappeared.